Economic inequality, income, and their effects on electoral and civil society participation in authoritarian regimes - Lott, Lars (Zeitschrift für vergleichende Politikwissenschaft, 2020)
What effect does economic inequality in authoritarian regimes have upon the political participation of its citizens? Do individual income and repression each have a greater effect than economic inequality? Three prominent theories, namely the Conflict, Relative Power, and Resource Theories address the inequality-participation puzzle in the context of democracies. However, theoretical arguments and empirical evidence for non-democratic regimes are scarce. I argue that it is individual income and the level of repression rather than economic inequality that explain political participation in autocracies. Using three-level hierarchical models that combine micro and macro level data for 65,000 individuals covering a various set of 31 authoritarian regimes and 54 country-years, this analysis demonstrates that higher levels of economic inequality hardly suppress political participation among all citizens. However, individual income has a more powerfully effect on civil society participation, while the level of repression decreases the voting likelihood more powerful than income. These findings suggest that the Resource Theory generates the greatest empirical support for autocracies.
Gesehen am 16.02.2021